Single- and dual-band filtering-response power dividers embedded SIW filter with improved output isolation - Kaijun Song (Nature Portfolio, 2017)
Abstract Two filtering-response power dividers embedded substrate integrated waveguide (SIW) filter are presented in this paper. By employing different SIW resonators, single- and dual-band filtering response are achieved, respectively. The even- and odd-mode method and the coupled resonator theory are applied to analyze the presented power dividers. In addition, a novel isolation technique using multiple isolation resistors is proposed to improve the output isolation performance of the filtering-response power divider with multiple resonators. To verify the proposed circuits, the single- and dual-band filtering-response power dividers are designed, fabricated and measured. Reasonable agreement between the simulated and measured results is achieved. Moreover, the measured output isolation of the fabricated dual-band filtering-response power divider with multiple resonators is about 20 dB, which demonstrates the theoretical predication.